The applications of International Classification of Funtioning, Disability and Health (ICF) by World Health Organization (WHO) in rehabilitation medicine practice - Abdul Latif, Lydia; Nazihah, H. (Faculty of Medicine, University of Malaya, 2007)
Context: Rehabilitation Medicine is dedicated to optimise patients function and health in the most comprehensive manner. ICF, the latest International Classification by World Health Organization (WHO) is a conceptual framework for the assessment of functioning, disability and health. The purpose of this paper is to describe the applications of ICF in Rehabilitation Medicine practice in the Medical Rehabilitation Unit, University of Malaya Medical Centre (UMMC), Kuala Lumpur. Issues: ICF consists of body function, structure, activity, participation and environmental factor. ICF categories are exhaustive, but are not practical to be used entirely and not applicable in clinical practice on their own. How is ICF used from the clinical perspective? It has to be adapted to make it usable. In Rehabilitation Medicine settings, the following are ways ICF is applied in clinical practice: research in terms of validating the use of available ICF Core Sets and development of new ICF Core Set; clinical practice based on the ICF-based sheet; and educational tools. Conclusion: The practice of Rehabilitation Medicine is in line and compatible with the concept of ICF and can serve as a new important language that can improve the practice of Rehabilitation Medicine. It can be a universal language in functioning, disability and health and can improve understanding in addressing issues on disability within the medical community, improve multi professionals’ communication among patients, healthcare providers and stakeholders.